Identification of major QTLs for seed vigor and growth-related traits using a biparental population in soybean - Kumar, Neeraj; Smith, James R.; Ray, Jeffery D.; Gillman, Jason D.; Bellaloui, Nacer (Frontiers in Genetics, 2026)
Soybean [Glycine max (L.) Merr.] is one of the most widely cultivated crops globally and serves as a primary source of plant-based protein and oil for human consumption. Seed vigor is a critical trait for germination and rapid seedling establishment, especially under sub-optimal environmental conditions. Genetic control of seed vigor measured as accelerated aging (AA%) was investigated using a quantitative trait locus (QTL) mapping approach. Associations of AA with six other traits: pubescence color (PC), beginning bloom (R1), reproductive period (RP), maturity (R8), plant height (PH), and stem termination (ST) were examined. A recombinant inbred line (RIL) population (247 F6-derived RILs) from a cross between DS25-1 and DT97-4290 was developed and genotyped using genotyping-by-sequencing (GBS), which yielded a set of 8,445 curated single-nucleotide polymorphism (SNP) markers from ∼90,000 SNPs. A subset of 201 RILs was phenotyped in Stoneville, Mississippi, over 3 years (2017–2019). A molecular linkage map was constructed using the SNP marker dataset, and composite interval mapping was performed using the R/qtl package. In total, 33 QTLs associated with seven phenotypic traits were identified across 12 chromosomes, using means of individual environments and best linear unbiased prediction (BLUP). Phenotypic variation of individual QTLs ranged from 0.56% to 89.77%, and the additive effects varied from −10.52% to 15.12%. Twelve QTLs detected across multiple environments on Gm03, Gm06, Gm07, and Gm19 were classified as stable. Notably, four genomic regions demonstrated QTL co-localization: Gm06 (all traits except ST), Gm07 (AA, R1, RP, and R8), Gm03 (AA and R1), and Gm19 (PH, R8, and ST). Major QTLs were in proximity to previously known genes: the T locus for pubescence color (Gm06), E1 (Gm06) and E11 (Gm07) loci for flowering and maturity, and Dt1 (Gm19) for stem termination. The closest SNPs associated with stable QTLs can be used to develop KASP markers for marker-assisted selection programs.